2016
DOI: 10.1016/j.aquatox.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Diatom-derived oxylipins induce cell death in sea urchin embryos activating caspase-8 and caspase 3/7

Abstract: a b s t r a c tDiatoms are an important class of unicellular algae that produce bioactive secondary metabolites with cytotoxic activity collectively termed oxylipins, including polyunsaturated aldehydes (PUAs), hydroxyacids (HEPEs), oxo-acids and epoxyalcohols. Previous results showed that at higher concentrations, the PUA decadienal induced apoptosis on copepods and sea urchin embryos via caspase-3 activation; at lower concentrations decadienal affected the expression levels of the caspase-8 gene in embryos o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 110 publications
2
33
0
1
Order By: Relevance
“…Initial studies were performed using single PUAs at low concentrations, demonstrating that decadienal, heptadienal, and octadienal exerted toxigenic effects on embryo development [30]. The strongest effect was induced by decadienal, with heptadienal and octadienal requiring higher concentrations to reach the same effects as decadienal [32]. By contrast, HEPEs induced developmental malformations at much higher concentrations when compared to PUAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial studies were performed using single PUAs at low concentrations, demonstrating that decadienal, heptadienal, and octadienal exerted toxigenic effects on embryo development [30]. The strongest effect was induced by decadienal, with heptadienal and octadienal requiring higher concentrations to reach the same effects as decadienal [32]. By contrast, HEPEs induced developmental malformations at much higher concentrations when compared to PUAs.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few studies are available on natural toxins and on the possible effects of mixtures of these toxins on marine organisms. Oxylipins are a well-known class of diatom secondary metabolites that have been studied for their capability to induce reproductive failure in several marine invertebrates [10,[24][25][26][27], including sea urchin Paracentrotus lividus [28][29][30][31][32]. Oxylipins represent a group of diverse compounds deriving from the oxidation of polyunsatured fatty acids that are released after cell damage or senescence [11,12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results expand previous investigations on the negative effects of lithium on the embryogenesis of sea urchin embryos. Sea urchins have been widely used as sensitive indicators of biochemical, morphological and physiological changes linked to environmental stressors, such as pesticides, heavy metals, ionizing radiations, ocean warming and acidification, metal nanoparticles and natural toxins 42 45 66 67 68 69 70 71 72 73 74 75 . Our results have shown that lithium is able to induce malformations in sea P. lividus urchin embryos, exerting a strong effect if the treatment is made before fertilization at concentrations much lower than those applied after fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Большинство видов диато-мей продуцируют по меньшей мере 2 класса оксилипинов, полиненасыщенные альдегиды и нелетучие оксилипины. Эти компоненты могут действовать как сдерживающий консументов фактор, нарушая их репродуктивный процесс [38], повышая смертность самок [21], уменьшая биомассу [14], повреждая ранние личиночные стадии развития (в экспериментах) [14,17,24,57,72].…”
Section: сигналинг в водных экосистемахunclassified